Chronic pain during pregnancy: a review of the literature - Ray-Griffith SL; Wendel MP; Stowe ZN; Magann EF (Dove Medical Press, 2018)
Shona L Ray-Griffith,1,2 Michael P Wendel,2 Zachary N Stowe,3 Everett F Magann2 1Department of Psychiatry, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 2Department of Obstetrics and Gynecology, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 3Department of Psychiatry, University of Wisconsin-Madison, Madison, WI, USA Background and purpose: The majority of the reviews and studies on chronic pain in pregnancy have primarily focused on the pharmacological and non-pharmacological treatment options. The purpose of our review was to identify evidence-based clinical research for the evaluation and management of preexisting chronic pain in pregnancy, chronic pain associated with pregnancy, and chronic pain in relation to mode of delivery. Methods: A literature search was undertaken using the search engines PubMed, CINAHL, EBSCOhost, and Web of Science. Search terms used included “chronic pain” AND “pregnant OR pregnancy” OR “pregnancy complications” from inception through August 2016. Results: The basis of this review was the 144 articles that met inclusion criteria for this review. Based on our review of the current literature, we recommend 7 guidelines for chronic pain management during and after pregnancy: 1) complete history and physical examination; 2) monitor patients for alcohol, nicotine, and substance use; 3) collaborate with patient to set treatment goals; 4) develop a management plan; 5) for opioids, use lowest effective dose; 6) formulate a pain management plan for labor and delivery; and 7) discuss reproductive health with women with chronic pain. Conclusion: The management of chronic pain associated with pregnancy is understudied. Obstetrical providers primarily manage chronic pain during pregnancy. Some general guidelines are provided for those health care providers until more information is available. Keywords: chronic pain, pregnancy, pregnancy complications, chronic pain in pregnancy, guidelines for pain in pregnancy, pain management in pregnancy